Combinatory problems in numerical semigroups - Torrão, Denise Miriam Mendes (2019)
This thesis is devoted to the study of the theory of numerical semigroups. First, the focus is on saturated numerical semigroups. We will give algorithms that allows us to compute, for a given integer g (respectively integer F), the set of all saturated numerical semigroups with genus g (respectivaly with Frobenius number F). After that, we will solve the Frobenius problem for three particular classes of numerical semigroups: Mersenne, Thabit and Repunit numerical semigroups. Lastly, we will characterize and study the digital semigroups and the bracelet monoids; Resumo: Problemas Combinat´orios em Semigrupos Num´ericos Esta tese ´e dedicada ao estudo da teoria dos semigrupos num´ericos. O primeiro foco ´e o estudo dos semigrupos num´ericos saturados. Daremos algoritmos que nos ir˜ao permitir calcular, dado um inteiro g (repectivamente, um inteiro F), o conjunto de todos os semigrupos num´ericos saturados com g´enero g (respectivamente, com n´umero de Frobenius F). Depois disso, iremos resolver o problema de Frobenius para trˆes classes particulares de semigrupos num´ericos: semigrupos num´ericos de Mersenne, de Thabit e de Repunit. Por fim, iremos caracterizar e estudar os semigrupos digitais e os mon´oides braceletes.